Er det stygt å seie neger? Om konnotasjonar, bruksmarkering og nemne for folkegrupper - Grønvik, Oddrun (LexicoNordica, 2002)
In this article, the author discusses the lexicographical challenges inherent in dealing with what is generally termed sensitive vocabulary, such as words for minority groups amongst language users. The starting point is recent evidence of changing attitudes in Norway to some such words, in particular the word neger (negro). The lexicographical treatment of this word and its near-synonyms is compared to developments in the treatment of words for older ethnic minorities in the region (same, finn, lapp; sigøynar, tater, rom(ani); jøde). The author argues that a good monolingual dictionary gives as accurate a reflection as possible of the vocabulary of the language it purports to describe, in a way which is immediately recognisable and acceptable to the users of that language. This lexicographic mirror image must comprise both denotative and connotative usage. Changes in attitude to vocabulary amongst dictionary users therefore require competent handling by dictionary editors. Some methods are suggested and commented on for dealing with the type of vocabulary discussed here.